Variables that Influence in Management of the Cikapundung Sub-Watershed - Fardani, Irland; Kurniasari, Nia; Tri Aryanto, Teguh; Rachmatika, Shafa; Luthfiyah Salsabila, Syifa; Syahda Putri, Nabila; Fajar Ramadhan, Mochamad; Gustiayadi, Danyar; Aras Puspitasari , Indah (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2024)
The Cikapundung Sub-Watershed is a source of clean water for people living in Bandung City. The Cikapundung Sub-Watershed has several main problems, such as land change, landslides, and land damage. Many efforts have been made to improve the conditions of the Cikapundung sub-district by the government, the community, and Non-Governmental Organizations (NGOs). However, these efforts have not achieved satisfactory results. This occurs due to the inaccuracy of handling by each stakeholder regarding the variables that influence the conditions of the Cikapundung sub-district. This research aims to determine the variables that have the most influence on the management of the Cikapundung Sub-Watershed. This research uses Micmac analysis to identify the most influential variables within an ecosystem. From the research results, it appears that whether indirect influence or indirect influence, the variables of Society Participation and Local Wisdom are the most influential variables in the management of the Cikapundung sub-basin. These two variables are in a position that has a strong influence on other variables and has a low level of dependence on other variables.